What Is Steam Education? - Koychiyeva Zarnigor Abdumannob qizi (Peerian Journals Publishing, 2022)
This article provides insights into STEAM education, its specific features and functions. Recommendations for the introduction of STEAM education in secondary schools are given
Keywords: STEAM; interactive methods; ICT; pedagogical technologies